Diversity and Efficacy Mold Rhizosphere to Control Lasiodiplodia theobromae Causing Stem-End Rot Disease on Citrus nobilis from East Kalimantan: Diversity and Efficacy Mold Rhizosphere to Control Lasiodiplodia theobromae - Agustina, Nensi; Mutia Erti Dwiastuti; Triwiratno , Anang; Suharjono (Journal of Tropical Life Science, 2024)
The current study aimed to determine the abundance and diversity of soil characteristics and their relationship with mold abundance and potential in inhibiting Lasiodiplodia theobromae, a potential rhizosphere mold species of Siamese orange plant. The pathogenic mold that causes stem-end rot disease was isolated from stems with rotting symptoms. In contrast, the antagonistic mold was obtained from isolation from the rhizosphere soil of Siamese plants. The samples were collected from Siamese orchards in East Kalimantan. The abundance and diversity of molds on swamp land are higher than on dry land. A total of 28 molds were found in the rhizosphere of Siamese orange plants. Mold abundance was positively correlated with soil moisture, organic matter, C-Organic, and N-total but negatively correlated with temperature and pH. Soil chemical characteristics directly influence mold abundance, while soil chemical characteristics indirectly influence it. 21 out of 28 isolates were Biological Control Agents (BCA). TR37 mold has the highest inhibitory power of 89.31% of the D13.C2 pathogen that causes stem-end rot disease. ITS rDNA sequence homology shows that the TR37 mold identified as Trichoderma reesei, while pathogen Lasiodiplodia theobromae causes stem-end rot disease